A phenomenological research of the motivational factors of kendo practitioners in Serbia - Dumić, Milan (2016)
Kendo is a Japanese martial art that has been gaining interest over the past couple of decades and is considered as one of the most popular budo martial arts. The purpose of this study was to understand and explain what motivates highly skilled kendo practitioners to practice and compete, and how did their sources of motivation change throughout their kendo engagement. Phenomenological approach was used to look into the experiences of kendo practitioners in order to understand better their motivation behind this martial art. Semi-structured interviews were conducted with eight kendo practitioners from Serbia in their native language. Before data collection, a pilot study was conducted, and the researcher underwent a bracketing interview. Self-determination theory and achievement goal theory were used for explaining the results. The findings revealed that participants practise kendo to satisfy personal needs (e.g., need for sports activity, interest in Japanese culture, and past sports experience) driven by extrinsic sources of motivation (identified and integrated regulation). When the needs for autonomy, competence and relatedness were satisfied, participants were motivated to engage in kendo activity out of their choosing without pressure, hence practicing kendo out of pure enjoyment driven by intrinsic motives. This is explained with the fact that kendo is integrated into participants lives, acting as a great coping tool, promoting constant development and personal growth. Interestingly, younger kendo practitioners exhibited both ego and task objectives orientations emphasizing competition goals, while older and more experienced kendo practitioners are focused more on mastery goals. Findings of the present study give us an insight regarding motivation of kendo practitioners, and other martial arts practices across the world. These qualitative information is helpful to sensei’s and sport professionals who want to work in this unique environment.